Fluindione and cefixime induced cutaneous bleeding manifestations A case report and review of literature - Anandabaskar, Nishanthi; Jayabalan, Nalinidevi; Jayaraman, Mohanasundaram; Rajamohammad, Meher Ali (International Journal of Pharmacological Research, 2018)
Fluindione an oral vitamin K antagonist is associated with various hemorrhagic and immunoallergic effects. This drug is also prone to produce various drug interactions, which if not taken into consideration while prescribing, might lead to increased incidence of adverse drug reactions for the patients. We report a case of drug interaction between fluindione and cefixime leading to cutaneous bleeding manifestations and raised PT-INR. Our patient was a 59 year old lady, a known case of rheumatic heart disease and mitral valve replacement, on tablet fluindione 20 mg for past 11 years. She was prescribed tablet cefixime 200 mg two times a day for three days for treatment of upper respiratory tract infection, following which she developed cutaneous bleeding manifestations like ecchymosis and purpura in left upper and lower limbs. She also had a rise in PT-INR level to 4.2, predisposing the patient to life threatening bleeding manifestations. Hence, caution is warranted while prescribing antibiotics to patients on oral anticoagulant therapy. Antibiotics that do not cause drug interaction with the anticoagulants must be selected in these patients. Also, periodic monitoring of PT INR in patients on anticoagulants especially when a new drug is co-prescribed is essential to curb the hazards of potential adverse drug interaction.